Hands-on parallel & distributed computing with Raspberry Pi devices and clusters - Shoop, Elizabeth; Matthews, Suzanne J.; Brown, Richard; Adams, Joel C. (Journal of parallel and distributed computing, 2025)
Parallel and distributed computing (PDC) concepts are now required topics for accredited undergraduate computer science programs. However, introducing PDC into the CS curriculum is challenging for several reasons, including an instructor's lack of PDC knowledge and difficulties in accessing PDC hardware. This paper addresses both of these challenges by presenting free, interactive, web-based PDC teaching modules using inexpensive Raspberry Pi single board computers (SBCs). Our materials include a free disk image that makes it possible for instructors to build Raspberry Pi clusters in minutes and use our software in a variety of curricular contexts. Our multi-year assessment of these materials on students and faculty members indicates that: (i) our materials increased students' confidence regarding important PDC concepts and motivated them to study PDC further; and (ii) our materials increased faculty members' confidence and preparedness in teaching key PDC concepts at their own institutions. •Free online interactive modules for learning PDC with Raspberry Pis and Pi clusters.•Self-organizing cluster: connects disparate Pis into a working cluster in minutes.•Free disk image pre-loaded with all activities for painless classroom adoption.•Our materials increase student confidence about PDC and motivation to learn more PDC.•Our materials increase faculty confidence and preparedness to teach PDC.